Development of Module Based on Local Wisdom of Grenden Village to Improve Students Critical Thinking Skills in Junior High School Science Learning - Wahyuni*, Sri; Rifqi, Ahmad Hisyam; Yusmar, Firdha; Sya'adah, Himatus (Universitas Syiah Kuala, 2025)
Critical thinking skills (CTS) are one of the important aspects that need to be developed because in reality students still have difficulty in developing these skills so that it has an impact on their ability to analyse information and solve problems. The purpose of this research is to obtain a module that is valid, practical, and effective in improving students' CTS. This research is a research and development (RD) study that uses the ADDIE research model. Data were collected through validation sheet, learning implementation sheet, test sheet, and student response questionnaire. The module validity analysis technique was obtained through validation sheets assessed by validators, module practicality analysis was obtained through learning implementation sheets assessed by observers, and module effectiveness analysis was obtained through test sheets and student response questionnaires. The results showed that the module obtained a validity value of 91.04% (very valid), a practicality value of 92.41% (very practical), and an effectiveness value through the test obtained an n-gain of 0.68 (medium category), and a response questionnaire of 87.92% (very good). It can be concluded that the module based on local wisdom of Grenden Village is valid, practical, and effective to improve students' CTS